WHY DID THE UKRAINIANS DISAPPEAR ON KUBAN? - ДМИТРО БІЛИЙ; ІВАН ПЕТРЕНКО (Cхід, 2021)
An issue, regarding famine (Holodomor) – genocide organization that was performed by the Soviet system on Kuban where the Ukrainians constituted majority, is considered in the article. The particular schemes of the deliberate policy oriented on physical annihilation of the Ukrainian population on Kuban, destruction of the national, ethnical and group (Cossacks’) identity, cessation of national-cultural development, forced russification, all abovementioned are the characteristics of genocide, the main features of which were determined by a particular UN resolution in 1948. The authors provide the particular data that reveal a deliberate policy of the USSR aimed at annihilation of the Ukrainians on the Northern Caucasus (Kuban). Provided factual data is based on the wide range of archival sources, testimonies of witnesses, publications of the scientific studies. The authors’ analysis permits to conclude that a deliberate policy was provided regarding the Ukrainians on Kuban that were an inherent part of the general Ukrainian national space during 1932-1933-s, namely the policy included mass physical annihilation via artificial famine, repressions, deportations as well as via different means of the Ukrainians’ denationalization. The processes were on the territory of the USRR as well as in the places of high concentration of the Ukrainians beyond its borders, particularly on the Northern Caucasus. The specific implications of the work are to highlight the methods that the Soviet government used against the Ukrainians on Kuban at the abovementioned period, the authors consider the measures as genocide based on the UN resolution of 1948, moreover, the analysis of the statistical data is provided to prove the scale of physical loss of the Ukrainians on Kuban. Considering that the scientific issue of the his-tory of the Ukrainians on the Northern Caucasus (Kuban) at the period of famine (Holodomor) du¬ring 1932-1933-s only begins to be reflected, the results of the article can be a base for the further studies and more deep consideration of one of the greatest disasters in the 20th century – Famine (Holodomor)-genocide of the Ukrainian nation.